Can match-mimicking intermittent practice be used as a simulatory training mode of competition using Olympic time frame in elite taekwondo athletes? - Chuang, S.-J.; Sung, Y.-C.; Chen, C.-Y.; Liao, Y.-H.; Chou, C.-C. (Frontiers in Physiology, 2019)
Aim: The physiological realities between Taekwondo (TKD) simulation kicking training and TKD competition according to the Olympic time frame remain unclear. The purpose of this study is to establish an Olympic match-simulated kicking model and compare its effects with real TKD competition on physiological challenges and hormonal responses during serial matches in elite athletes.